Mengatasi Kejenuhan Suami-Istri Perspektif Ulama Mazhab - Maloko, M. Thahir; Rahman, Arif (Mazahibuna: Jurnal Perbandingan Mazhab, 2020)
Making family in harmony is not as easy as we say. There are many obstacles faced by members of the family that sometimes make them bored. Those obstacles can be such as; business, different opinion, the presence of "third persons", misunderstanding, arrogance, jealousy and infertility. Besides that, economy and education obstacles can be also the cause of disharmony. Based on Islamic teaching, the strategic way to solve this problem is to refresh the hamony by appeciating and builiding mutual understanding among members of the family.